4x-3=-6x+4

Simple and best practice solution for 4x-3=-6x+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-3=-6x+4 equation:



4x-3=-6x+4
We move all terms to the left:
4x-3-(-6x+4)=0
We get rid of parentheses
4x+6x-4-3=0
We add all the numbers together, and all the variables
10x-7=0
We move all terms containing x to the left, all other terms to the right
10x=7
x=7/10
x=7/10

See similar equations:

| -9x=-2−10x | | -.65x+0.45x=5.4 | | -9z=-2−10z | | 7q=6q+10 | | 18x+54=18x+9 | | -18.2h+12.59=0.5h−4.51−19.7h | | 5x+16+8x-8=180 | | 19.1k=9.75+19.6k | | -13−19f=-20f | | 18j+16+8j=20j−20 | | 1+0,5x=2*(0,25x-3) | | -8y−10=9−7y | | -5v−9−5=10−9v | | 5x*5=0 | | -5b=-6b+4 | | 16+y=9y | | 3+7s=6s−7 | | (-a)/10-8=(-24) | | 5=2.5^n | | 10+6f=-f+4+6 | | -h=h−10 | | 56+9u=17u | | 65-3.6x/1000=-43 | | 2f+7f+9= | | -2n−9=9+7n | | 1+0.5x=2*(0.25x-3) | | (-x)/3+4=20 | | -9j−3=-10j | | 2d=-7d+9 | | 4n+20+2n+34=180 | | (2x-9)^2=162 | | 10+m=-4m |

Equations solver categories